The growth of the hide and seek botnet. Issue 3 (March 2019) - Haria, Sam
Abstract : Security researchers recently found a botnet that remains live and working, even after a device has been reset. 1 This malware has been named 'Hide and Seek' (HnS) and appears to be the world's first to survive a reboot, making it very persistent and extremely dangerous.